Specific exercise is medicine - Preventing and treating a peripheral neuropathy - Fiona Streckmann; Maryam Balke; Guido Cavaletti; Alexandra Toscanelli; Wilhelm Bloch; Bernhard F. Décard; Helmar C. Lehmann; Oliver Faude (Bern Open Publishing, 2023)
Introduction Neuropathies are a prevalent, heterogeneous group of diseases of the peripheral nervous system. Symptoms are often debilitating, difficult to treat, and usually become chronic. Not only do they diminish patients' quality of life, but they can also affect medical therapy and lead to complications. To date, for most conditions there are no evidence-based causal treatment options available. Specific exercise interventions have proven beneficial to reduce and even prevent a neuropathy. Objective Our objective in a systematic review with meta-analysis was to analyze exercise interventions for neuropathic patients in order to evaluate the potential benefits of exercise on neuropathies of different origin that can then be translated into practice. Methods Two independent reviewers performed a systematic review with meta-analysis according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). Inclusion criteria according to the PICOS approach were: neuropathic patients, exercise interventions only, an inactive or non-exercising control group, and solely randomized controlled trials with the following outcome parameters: neuropathic symptoms, balance parameters, functional mobility, gait, health-related quality of life, and HbA1c (glycated hemoglobin). Results A total of 41 randomized, controlled trials met all inclusion criteria, 20 could be included in the quantitative analysis. Study quality varied from moderate to high. Current data further support the hypothesis that exercise is beneficial for neuropathic patients. This is best documented for patients with diabetic peripheral neuropathy (DPN; 27 studies) as well as for chemotherapy-induced peripheral neuropathy (CIPN; nine studies), while there are only few studies (five) on all other causes of neuropathy. We found standardized mean differences in favor of the exercise group of 0.27-2.00 for static balance, Berg Balance Scale, Timed-up-and-go-test, nerve conduction velocity of peroneal and sural nerve as well as for HbA1c in patients with DPN, and standardized mean differences of 0.43-0.75 for static balance, quality of life, and neuropathy-induced symptoms in patients with CIPN. Conclusion For DPN, evidence-based recommendations can now be made, suggesting a combination of endurance and sensorimotor training to be most beneficial. For patients with CIPN, sensorimotor training remains the most crucial component. For all other neuropathies, more high-quality research is needed to derive evidence-based recommendations. Overall, it seems that sensorimotor training has great potential to target most neuropathies and combined with endurance training is therefore currently the best treatment option for neuropathies.